Bestiarium Judaicum : Unnatural Histories of the Jews - Geller, Jay, 1953- (Book collections on Project MUSE., 2017)
Through close textual analysis, detailed historical contextualization, and critical animal theory Bestiarium Judaicum examines how and to what ends German-Jewish writers (including Freud, Heine, and Kafka) drew upon the vast inventory of verbal and visual images of nonhuman animals disseminated for millennia to bestialize, debase, and justify the persecution of Jews.